Calcule o valor da expressão:
2 ⁻¹ ₋ (-2) ⁻² + (-2)⁻¹ / 2² + 2⁻² =
Resolva:
- ( 1/4) ⁻⁴ =
Soluções para a tarefa
Respondido por
1
Calcule o valor da expressão:2 ⁻¹ ₋ (-2) ⁻² + (-2)⁻¹ / 2² + 2⁻² =
Resolva:
- ( 1/4) ⁻⁴ =
Resolva:
- ( 1/4) ⁻⁴ =
Anexos:
![](https://pt-static.z-dn.net/files/dfe/65efbd7b4e9ade163fe53ed4b94c5e3a.jpg)
MarleeTames:
Muito obrigada!
Perguntas interessantes
Química,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Inglês,
1 ano atrás